Perbandingan Beton Normal Dengan Beton Menggunakan Abu Vulkanik Gunung Semeru Ditinjau Dari Kuat Tekan Dan Setting Time - Nurul Rochmah; Ahmad Lukman Ariansyah; Dewi Pertiwi (Institut Teknologi Adhi Tama Surabaya, 2023)
Heavy metal chemicals can be found in the volcanic ash from Mount Semeru's eruption. The content of heavy metals such as silica, alumina, iron, and lime can bind cement to concrete. Nowadays, volcanic ash that comes out of volcanic eruptions is used as a reducing material for cement. Some cement materials for concrete mixtures are viewed through the lens of concrete compressive strength. It was attempted to use volcanic ash from Mount Semeru to reduce cement material in concrete with an FC of 20 MPa. This study aims to determine the setting time and compare the compressive strength of concrete. It used a cylindrical test object with a diameter of 100 mm and a height of 200 mm. Each variation had three test objects. The test results indicated that the setting time for normal concrete was 195 minutes; AV variations of 45% got 225 minutes, or a 30-minute delay, from normal concrete; and 50% of AV variations got 255 minutes, or a 60-minute delay. Meanwhile, the average compressive strength test for normal concrete aged 28 days was 19.18 MPa, and the variation of AV concrete aged 45% gained 5.78 MPa or decreased by 30.12% of normal concrete. The average compressive strength in AV concrete aged 50% for 28 days was 5.83 MPa, or 30.40% lower than normal concrete.